2017
DOI: 10.24191/jeeir.v5i2.8805
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining Islamic financial literacy among undergraduates

Abstract: This article is written to provide a deliberation reviews on the current context of Islamic financial literacy among students. A research was conducted through case studies carried out among the students of University Malaysia Sabah Campus W.P. Labuan and Institut Pendidikan Guru (IPG), Kampus Batu Lintang, Sarawak, a teacher training institute. The respondents are candidates to become teachers upon completing their studies. Being knowledgeable and having skill in financial literacy, especially with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
2
9
0
5
Order By: Relevance
“…Based on the hypothesis test through multiple linear regression method by using SPSS IBM Version 20 software, it is known that there are significant impacts of the variables of gender, age, education, and length of business toward the literacy rate of sharia finance of creative industry owners in Yogyakarta Special Region. This finding is inline with the results of research conducted by Bünyamin and Mutlu (2017) and Abdullah and Wahab (2017). The knowledge sharing to the creative industry is not merely emerging from the government, academics, or big business, however, knowledge sharing between creative industries could become the main key success of creative industry in developing amidst global trading era.…”
Section: The Understanding Of Literacy Rate Of Sharia Finance Based Osupporting
confidence: 83%
“…Based on the hypothesis test through multiple linear regression method by using SPSS IBM Version 20 software, it is known that there are significant impacts of the variables of gender, age, education, and length of business toward the literacy rate of sharia finance of creative industry owners in Yogyakarta Special Region. This finding is inline with the results of research conducted by Bünyamin and Mutlu (2017) and Abdullah and Wahab (2017). The knowledge sharing to the creative industry is not merely emerging from the government, academics, or big business, however, knowledge sharing between creative industries could become the main key success of creative industry in developing amidst global trading era.…”
Section: The Understanding Of Literacy Rate Of Sharia Finance Based Osupporting
confidence: 83%
“…Some studies have identified factors that influence the level of students' IFL. For instance, Abdullah et al (2017) suggested three factors: gender, education level and attitude to financial management. On the other hand, Rahim et al (2016) listed the factors that influence IFL among university students, identifying them to be religiosity, financial satisfaction and hopelessness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berdasarkan penelitian yang dilakukan oleh Bunyamin (2017), ditemukan bahwa tingkat literasi keuangan syari'ah seseorang dipengaruhi oleh faktor demografi seperti jenis kelamin, usia, tingkat pendapatan dan tingkat pendidikan. Sedangkan menurut penelitian yang dilakukan oleh (Abdullah, Wahab, Sabar, & Abu, 2017) hanya terdapat tiga variabel yang signifikan untuk menentukan tingkat literasi keuangan syari'ah seseorang yaitu sikap pada manajemen keuangan (AOPFM), jenis kelamin (Gender), dan Tingkat Pendidikan. Penelitian yang dilakukan oleh Setyawati & Suroso (2017), menunjukkan bahwa hanya usia, jenis kelamin, tingkat pendidikan, dan tempat tinggal yang mempengaruhi tingkat literasi keuangan syari'ah seseorang.…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang dilakukan oleh Abdullah et al (2017) hanya terdapat tiga variabel yang signifikan untuk menentukan tingkat literasi keuangan syari'ah seseorang yaitu sikap pada Manajemen Keuangan (AOPFM), jenis kelamin (Gender), dan Tingkat Pendidikan. Kiliyanni dan Sivaraman (2016) menemukan bahwa jenis kelamin, status perkawinan, usia, agama, tingkat pendidikan, disiplin studi, pengalaman kerja, pendapatan, pekertjaan orang tua, dan pendidikan orang tua berpengaruh terhadap tingkat literasi keuangan.…”
Section: Hubungan Faktor Demografi (Pendidikan) Terhadap Tingkat Literasi Keuangan Syari'ahunclassified